Myocardial protection after whole body heat stress in the rabbit is dependent on metabolic substrate and is related to the amount of the inducible 70-kD heat stress protein. - Marber, M S (1994)
The aims of this study were to examine the effects of whole body heat stress and subsequent stress protein induction on glycolytic metabolism, mitochondrial metabolism, and calcium handling within the heart. The effect of heat stress on glycolytic and mitochondrial pathways was examined by measuring contractile performance in the presence of glucose and pyruvate, respectively. Calcium handling was assessed using force-interval relationships. Right ventricular papillary muscles taken from heat-stressed and control rabbit hearts were superfused with Kreb's solution containing either glucose or pyruvate and rendered hypoxic for 30 min. After reoxygenation, the greatest recovery of contractile function occurred in the heat-stressed muscles with pyruvate as substrate; there was, however, no difference in the force-interval relationship between the groups. The degree of contractile recovery was related to the content of the inducible 70-kD but not the 65-kD, heat stress protein. This study suggests that heat stress enhances the ability of rabbit papillary muscle to use pyruvate, but not glucose, after reoxygenation, and that the differences seen in contractility may be secondary to induction of the 72-kD stress protein.